Optimization of osmotic dehydration of pineapple (Ananas comosus L.) using the response surface methodology (2011)
ABSTRACT: The response surface methodology was used to optimize the effects of temperature (25 - 45⁰C) and citric acid concentration (0.5 - 2.5% w/w) in osmotic dehydration of pineapple in a sucrose solution. A 32 factorial design was used with weight loss (WL, %), moisture loss (ML, %) and solid gain (SG, %) as responses. The models obtained for all the responses were significant (P≤0.05) without a significant lack of fit. The results suggest that WL, ML and SG can reach 42.62%, 36.54% and 292.16% respectively, after 4 to 6 h of the process, with 100% sensory acceptance and reductions in microbial counts of more than two log cycles, using the conditions defined by the optimization (44.99⁰C and 2.48% citric acid).